Dynamic Antenna Impedance Tuning for Sub-GHz Systems - Dorn, Christian; Pfannenmüller, Christof; Gabsteiger, Jasmin; Kurin, Thomas; Lurz, Fabian; Hagelauer, Amelie (2025 IEEE Topical Conference on Wireless Sensors and Sensor Networks, WiSNeT 2025, 2025)
In all wireless systems, high power transfer from the RF front-end (RFFE) to the antenna is required. To achieve this, impedance matching between the RFFE and the antenna is necessary. Most applications assume a static antenna impedance for a given frequency band and thus only require a single static matching network per band. In reality, changing near-field conditions (e.g. due to human interaction) require a rapid adaption or in-band mismatch requires a finer change in impedance matching. This work introduces and compares several topologies that allow dynamic adaptive antenna impedance tuning in sub-GHz applications. They even permit a strong mismatch with a voltage standing wave ratio (VSWR) of 20:1 with a high power rating suitable for transmission in mobile applications.
CRIS-Team Scopus Importer:2025-04-04
Keywords: antenna; impedance; tuning